Exogenous lipoid pneumonia: an important cause of interstitial lung disease in infants - Marangu, Diana (Respirol Case Rep, 2018)
Exogenous lipoid pneumonia (ELP), an important cause of interstitial lung disease, often goes unrecognized. We conducted a retrospective study of children with histologically confirmed ELP at Red Cross Children’s Hospital, South Africa. Twelve children of Zimbabwean heritage aged 2.1–10.8 months were identified between 2012 and 2017. Repeated oral administration of plant‐based oil for cultural reasons was reported by 10 of 11 caregivers. Cough (12/12), tachypnoea (11/12), hypoxia (9/12), and diffuse alveolar infiltrates on chest radiography (12/12) were common at presentation. Chest computed tomography revealed ground‐glass opacification with lower zone predominance (9/9) and interlobular septal thickening (8/9). Bronchoalveolar lavage specimens appeared cloudy/milky, with abundant lipid‐laden macrophages and extracellular lipid on Oil‐Red‐O staining (12/12), with polymicrobial (6/12) and Mycobacterium abscessus (2/12) co‐infection. Antibiotics, systemic corticosteroids, and therapeutic lavage were interventions in all eight and five patients, respectively. Clinicians should consider ELP in children with non‐resolving pneumonia in settings with similar practices.